Monitoring the agri-food system in Myanmar: Agricultural crop traders – September 2021 survey - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
To understand the effects of COVID-19 and political instability on Myanmar’s crop trade sector, a phone survey of commodity traders was conducted in September 2021. Key Findings The most significant disruptions to crop trading in September were in banking and transportation. Sixty percent of respondents reported higher transportation costs and 47 percent reported difficulties making and receiving payments for crops, respectively. Sixty-one percent of traders reported difficulties collecting repayment from farmers on credit lent out. Although over half the sample offered credit to farmers in the 2021 monsoon season, there was an 8 percent decline relative to the 2020 monsoon season. Overall, 82 percent of the credit lent to farmers has not yet been repaid and 37 percent of traders do not expect full repayment before the 2022 monsoon season. There was also a 9 percent decline in the share of traders taking credit in during the 2021 monsoon season (15 percent) relative to 2020 (24 percent) and 44 percent of the traders taking credit do not expect to fully repay these debts before the 2022 monsoon season. Sixty-three percent of traders reported lower overall trade volumes in September 2021 relative to the same time in 2020. For the main crop traded, average daily turnover was down by 5 percent and storage volumes were down by 6 percent. Hired transportation costs increased by an average of 23 percent relative to September 2020 and 56 percent of traders reported fewer trips to buy crops. Looking ahead If these hurdles persist into the monsoon marketing season, they will present challenges to farmers as they try to sell their harvests. Indeed, there are already signs of reduced marketing opportunities in September going into the harvest season. Removal of curfews and travel restrictions at each administrative level would lessen some of the marketing challenges. Delayed repayment of farmer credit combined with a heavy dependency on cash for transactions may lead to a cycle of reduced credit to farmers for winter and summer seasons.